Survival of coxsackievirus B3 under diverse environmental conditions. - McGeady, M L (1979)
The survival of coxsackievirus B3 was studied under various conditions of incubation. The comparative study demonstrated that coxsackievirus B3 was stable for 24h (less than 0.4-log decrease in titer) when suspended at neutral pH (6 or 23 degrees C) in the presence of 0.25% bovine serum albumin in saline regardless of whether the preparations were subjected to evaporation. Bovine serum albumin provided increased stability to the virus for each of the conditions tested. At 37 degrees C, evaporation greatly reduced the virus infectivity between 6 and 20 h of incubation. Nevertheless, coxsackievirus B3 was found to be stable for at least 24 h under conditions similar to those of a household environment, and its presence represents a potential biohazard to nonimmune persons. These data provide a rationale for using coxsackievirus B3 as a model for investigating the role of environmental surfaces in the transmission of enteroviral diseases.